Preparation of elementary school teacher for patriotic education in conditions of updating primary education (Pedagogy of Higher and Secondary Education, 2014)
Filimonova T. V. Preparation of elementary school teacher for patriotic education in conditions of updating primary education.The article covers theoretically reasonable issues concerning preparing elementary school teachers with regard to patriotic education of pupils in conditions of updating primary education. The article also considers the essence of the concept “preparing elementary school teachers for patriotic education of pupils”.
Keywords: future teachers; patriotic training; patriotic upbringing; patriotic education